A Combined Effect of Plasmon Energy Transfer and Recombination Barrier in a Novel TiO2/MgO/Ag Working Electrode for Dye-Sensitized Solar Cells. (6th September 2015) - Photiphitak, Chanu; Rakkwamsuk, Pattana; Muthitamongkol, Pennapa; Thanachayanont, Chanchana
Abstract : Novel TiO2 /MgO/Ag composite electrodes were applied as working electrodes of dye-sensitized solar cells (DSSCs). The TiO2 /MgO/Ag composite films were prepared by dip coating method for MgO thin films and photoreduction method for Ag nanoparticles. The MgO film thicknesses and the Ag nanoparticle sizes were in ranges of 0.08–0.46 nm and 4.4–38.6 nm, respectively. The TiO2 /MgO/Ag composite films were characterized by X-ray diffraction, scanning electron microscopy, and transmission electron microscopy. The TiO2 /MgO/Ag composite electrodes were sensitized by immersing in a 0.3 mM of N719 dye solution and fabricated for conventional DSSCs.J -V characteristics of the TiO2 /MgO/Ag DSSCs showed that the MgO film thickness of 0.1 nm and the Ag nanoparticle size of 4.4 nm resulted in maximum short circuit current density and efficiency of 8.6 mA/cm 2 and 5.2%, respectively. Electrochemical Impedance Spectroscopy showed that such values of short circuit current density and efficiency were optimal values obtained from plasmon energy transfer by 4.4 nm Ag nanoparticles and recombination barrier by the ultrathin MgO film.